Теоретичні аспекти формуванняекономічної безпеки підприємства - Жилін, І. М.; Zhylin, l. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
Визначено, що термін "безпека" широко вживається в усіх життєво важливих сферах суспільної діяльності та має значну кількість класифікаційних ознак. Безпековий дискурс сталого розвитку країни фокусується на концепції"національної безпеки", яка уособлює міжнародні відносини між державами, окремими підприємствами та спільнотами. Національна безпека держави та економічна безпека підприємства не протиставлені один одному, а взаємнодоповнені, адже лише ті підприємства можуть бути стійкими до загроз, де держава гарантує захист їх інтересів відризиків в єдиній економічній структурі державного устрою. Встановлено, що економічна безпека підприємств грунтується на двох підсистемах економічного розвитку —захисту та уповноваження прав на забезпечення гарантій безпеки, які є взаємопідсилюючими заходами передбачен-ня потенційних загроз. Широкий спектр наукових поглядів на сутність економічної безпеки підприємства пов'язаний з різними підходами до її структури, а саме сукупності елементів забезпечення безпеки, які формують без пекову модель економічного розвитку підприємства. Це дозволяє виокремити правовий, конкурентний, ресурсно-функціональний, індикативний, програмно-цільовий та безпековий підходи, які забезпечують стійкий стан економічної безпеки підприємства. It is determined that the term "safety" is widely used in all vital areas of public activity and has a significant number of classification features. The safety discourse of a country's sustainable development focuses on the concept of "national safety", which embodies international relations between states, individual enterprises and communities. The national safety of the state and the economic safety of the enterprise are not opposed to each other, but are mutually complementary, because only those enterprises can be resistant to threats where the state guarantees the protection of their interests from risks in the unified economic structure of the state system. It is established that the economic safety of enterprises is based on two subsystems of economic development —protection and empowerment of rights to safety guarantees, which are mutually reinforcing measures to anticipate potential threats. A wide range of scientific views on the essence of economic safety of an enterprise is associated with different approaches to its structure, namely, the set of safety elements that form the safety model of economic development of an enterprise. This makes it possible to distinguish legal, competitive, resource-functional, indicative, programmer—oriented and protective approaches that ensure a stable state of economic safety of an enterprise. From the standpoint of expanding the categorical apparatus of the study, we propose our own interpretation of the concept of "economic safety of enterprise" as a process that combines five main components: the result of the introduction of innovative production technologies to ensure stable market demand for products and obtaining benefits in the current and future periods; ensuring a stable economic condition, provided that internal risks and external threats are neutralized; the ability to diagnose financial and economic criteria for development and identify sources of dangerous manifestations; application of anti-crisis measures to neutralize internal and external threats; formation of competitive advantages and ensuring economic balance at all stages of the economic cycle. The article develops a model of formation of economic safety of agricultural enterprises, which reflects the organizational and economic mechanism of ensuring sustainable development of economic entities and conducting agribusiness in the face of threats and uncertainties. The timely prevention of threats in the agricultural sector can protect enterprises from economic recession, provided that hazards are detected, identified and neutralized in a timely manner. The focus of the economic safety of agricultural enterprises should be on productivity and resource saving to ensure the quality of the economic process and the continuous increase of opportunities for sustainable development.
Theoretical aspects of the formation of economic safety of the enterprise
Keywords: Безпека; Safety; економічна безпека підприємства; economic safety of the enterprise; конкурентні переваги; competitive advantages; національна безпека; national safety; сталий розвиток; sustainable development; ресурси; resources; ризики; risks; сільське господарство; agriculture